1997
DOI: 10.1063/1.473715
|View full text |Cite
|
Sign up to set email alerts
|

Level-dependent damping in intermolecular vibrations: Linear spectroscopy

Abstract: A theoretical investigation of the temperature dependence of the optical Kerr effect and Raman spectroscopy of liquid CS 2 A combined instantaneous normal mode and time correlation function description of the optical Kerr effect and Raman spectroscopy of liquid CS 2 A treatment of stimulated Raman intermolecular spectroscopy is presented that employs a Landau-Teller model of damping. This model incorporates a quantum-number dependence to population relaxation and pure dephasing, thereby introducing a specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
88
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(94 citation statements)
references
References 59 publications
(97 reference statements)
5
88
1
Order By: Relevance
“…In vibrational spectroscopies population and phase relaxation are often modeled by phenomenological level-dependent decay rates, that can be included in a perturbative treatment without major problems. 9,[60][61][62][63] However, these rates reflect the intermolecular dynamics in a rather indirect way, since they rely on the assumption of a white heat bath spectrum. Frequency fluctuations with a finite correlation time can be described by the stochastic model of Anderson and Kubo.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…In vibrational spectroscopies population and phase relaxation are often modeled by phenomenological level-dependent decay rates, that can be included in a perturbative treatment without major problems. 9,[60][61][62][63] However, these rates reflect the intermolecular dynamics in a rather indirect way, since they rely on the assumption of a white heat bath spectrum. Frequency fluctuations with a finite correlation time can be described by the stochastic model of Anderson and Kubo.…”
Section: )mentioning
confidence: 99%
“…49) Although the Fokker-Planck approach can be applied to any potential, we restrict ourselves in this pilot study to a harmonic coordinate, since different relaxation processes have been investigated for this system in great detail. 5,8,63,[67][68][69][70][71][72][84][85][86][87][88][89] It is then in principle possible to solve the integral for the potential kernel [eq. (8)] analytically: the first term on the r.h.s of eq.…”
Section: )mentioning
confidence: 99%
“…The low-frequency Raman spectrum of benzene has been studied extensively in both the time and frequency domains through experiments 8,9,[13][14][15][16][17][18][19][20][21][22][23][24] and molecular simulations. 11,18,[25][26][27][28] McMorrow and Lotshaw observed the broad, flattened shape of the benzene OKE spectrum in 1993, and on a preliminary basis concluded that the spectral features are a result of collective modes arising from molecular aggregates.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the assumption that ⌸ ( j) (q) decreases quickly with increasing j may not be as valid for intermolecular modes as it is for intramolecular modes. 38 For instance, we have evidence from simulations that while the value of ⌸ (2) (Q) for an intramolecular mode can be accurately predicted given knowledge of ⌸ (1) (Q), no such relationship holds for intermolecular modes. 39 Thus, C 2,2 (x;tЈ) may make a significant contribution to C(x;tЈ) that cannot be predicted based on knowledge of C 1,1 (x;tЈ).…”
Section: ͑3͒mentioning
confidence: 96%
“…37,38 There are two primary reasons why these other contributions may not be negligible. First, as is the case for intramolecular modes, there exist intermolecular modes whose symmetry dictates that ⌸ (1) (q)ϭ0 but for which ⌸ (2) (q) need not vanish.…”
Section: ͑3͒mentioning
confidence: 99%